SELF PRESENTATION ANGGOTA KOMUNITAS MOTOR RX-KING MRC (KAJIAN DRAMATURGI TENTANG PRESENTASI DIRI ANGGOTA KOMUNITAS MOTOR RX-KING DI KOTA SALATIGA) - Muhammad Bariqi Najman; Nurul Hasfi (Interaksi Online, 2019)
The RX-King motorcycle community is one of hundreds of well-known motorcycle communities in Indonesia. This community is seen as a frightening community because of the image of the RX-King itself which is famous as the "Jambret" motorcycle. The existence of this RX-King community actually wants to change the society stigma about this community which is considered negative. This can be seen from the activities inside and outside their community. In RX-King community scene, they have the characteristics of "revving up engine" and "giving a thumbs up" when they meet fellow RX-King motorcycle users on the road. The characteristic of the RX-King itself is often understood by the public as a negative thing, in fact it is a way of communicating between RX-King motorcycle users. The purpose of this study was to analyze the Self Presentation by members of the RX-King MRC motorcycle community in Salatiga City. This study uses a constructivist paradigm with descriptive qualitative research methods to see how the Front Stage and Back Stage of the RX-King community members MRC in the symbolic communication process. The theory used to describe this phenomenon is Goffman's dramaturgy and aspects of symbolic interactionism carried by George Herbert Mead. Informants in this study amounted to 6 people who are active members of the RX-King MRC community in Salatiga City who have different occupational backgrounds. The results of this study show that the front stage and back stage of MRC community members are very different. In the front stage the members of the RX-King MRC community conduct community activities that they usually do and in the back stage they carry out activities according to the routine that they usually do such as working and socializing in the community. By looking at actions, gestures, symbols, minds, self, we can see that members can match themselves according to conditions and situations. That the negative stigma attached to members of the RX-King MRC community is not entirely true because there are many positive activities including social service activities, charity activities, helping houses of worship that they always carry out in their community.